The Role of the Holy Quran in Promoting Rapprochement And Dialogue Between Religions - Al-Mohanna, Zaman Sahib Darwish (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Contemporary societies face rising religious tensions requiring solid theological foundations for peaceful coexistence. Specific Background: The Holy Qur’an articulates principles of tolerance, justice, moderation, freedom of belief, and respectful engagement with religious diversity, including dialogue with the People of the Book. Knowledge Gap: However, a concise and systematic formulation of these teachings as an integrated framework for present-day interfaith dialogue remains limited. Aims: This study examines Qur’anic verses and their contextual interpretations to construct a coherent model for rapprochement among religions. Results: Using a critical analytical literature review, the findings show that the Qur’an affirms rejection of coercion, recognition of plurality as divine wisdom, and cooperation based on shared human values. Novelty: The study synthesizes textual and contextual analysis into a structured Qur’anic framework applicable to contemporary plural societies. Implications: The results provide conceptual guidance for interfaith dialogue initiatives and educational programs fostering harmonious and inclusive communities. Highlights:• Establishes a Comprehensive Scriptural Model for Peaceful Coexistence Grounded in Divine Revelation.• Identifies Contextual Interpretation as Key to Overcoming Exclusivist Readings in Multi-Faith Settings.• Formulates Practical Guidance for Educational and Social Programs Promoting Mutual Understanding. Keywords: Holy Quran, Interfaith Dialogue, Religious Pluralism, Tolerance, Peaceful Coexistence